PERAN KUALITAS LAYANAN, CITRA LEMBAGA, DAN NILAI BAGI PELANGGAN TERHADAP KEPUASAN PELANGGAN SERTA DAMPAKNYA TERHADAP LOYALITAS (Studi Pada Mahasiswa Fakultas Ekonomi Unisbank Semarang) (Students' Journal of Economic and Management, 2013)
The purpose of the study entitled "The Role of Service Quality, Image Institute, and Value For Customers on Customer Satisfaction and Loyalty impact" is to investigate and analyze the role of service quality, the image of the institution, and customer value on customer satisfaction and its impact on loyalty. Population of 1097 students in the study of the withdrawal of a total sample of 100 respondents. The sampling technique used was purposive sampling sampling. The results of the hypothesis are: (1) The calculation of the statistical multiple linear regression analysis. (2) The calculation of the coefficient of determination of unity magnitude remaining 69.7% 30.3% influenced by other factors and coefficients of determination both remaining 79.2% 20.8% influenced by other factors. (3) The hypothesis in this research can be concluded that: a) the quality of service, the image of the institution and value for customers and a significant positive effect on customer satisfaction. b) quality of service, the image of the institution, to customer value and customer satisfaction, and a significant positive effect on loyalty. Stikubank University of Semarang in which case they should pay attention to the factors that influence loyalty, quality of service, the image of the institution, to customer value and customer satisfaction.Keywords: quality of service, the image of the institution, to customer value, customer satisfaction, loyalty.